cGAS-STING Pathway Does Not Promote Autoimmunity in Murine Models of SLE - Motwani, Mona; McGowan, Jason; Antonovitch, Jennifer; Gao, Kevin MingJie; Jiang, Zhaozhao; Sharma, Shruti; Baltus, Gretchen A.; Nickerson, Kevin M.; Marshak-Rothstein, Ann; Fitzgerald, Katherine A. (Frontiers in Immunology, 2021)
Detection of DNA is an important determinant of host-defense but also a driver of autoinflammatory and autoimmune diseases. Failure to degrade self-DNA in DNAseII or III(TREX1)-deficient mice results in activation of the cGAS-STING pathway. Deficiency of cGAS or STING in these murine models ameliorates embryonic lethality and polyarthritis in DNAseII-/- mice and myocarditis in Trex1-/- mice. However, the contribution of the cGAS-STING pathway, relative to endosomal TLRs, in systemic lupus erythematosus (SLE) is controversial. In fact, STING deficiency failed to rescue, and actually exacerbated, disease manifestations in Fas-deficient SLE-prone mice. We have now expanded these observations to a chronic model of SLE induced by the i.p. injection of TMPD (pristane). We found that both cGAS- and STING-deficiency not only failed to rescue mice from TMPD-induced SLE, but resulted in increased auto-antibody production and higher proteinuria levels compared to cGAS STING sufficient mice. Further, we generated cGASKOFaslpr mice on a pure MRL/Faslpr background using Crispr/Cas9 and found slightly exacerbated, and not attenuated, disease. We hypothesized that the cGAS-STING pathway constrains TLR activation, and thereby limits autoimmune manifestations in these two models. Consistent with this premise, mice lacking cGAS and Unc93b1 or STING and Unc93b1 developed minimal systemic autoimmunity as compared to cGAS or STING single knock out animals. Nevertheless, TMPD-driven lupus in B6 mice was abrogated upon AAV-delivery of DNase I. Overall, this study underscores that the cGAS-STING pathway does not drive systemic autoimmune disease in murine models of SLE. These data have important implications for cGAS-STING-directed therapies being developed for the treatment of systemic autoimmunity.